Measurement of Power Grid Resilience Based on a Dynamic Inoperability Input–Output Model - Wang, Yan; Gao, Shan; Wang, Fuzhang (Frontiers in Physics, 2022)
With the increase of global natural disasters, emergencies and terrorist attacks, it brings great challenges to the flexible operation of power grid. The research on the flexibility of power grid becomes more and more important. At the same time, the rapid development of renewable energy and smart grid also provides new opportunities for the research of flexible power grid. Based on the dynamic inoperability input-output model (DIIM), this paper creatively uses the node transmission power to represent the relationship between nodes in the power grid, and then studies the resilience measurement of the power grid. Firstly, the significance of studying power grid resilience is discussed, and the absorption and recovery capacity of power grid resilience is described; Secondly, the power grid resilience measurement model based on DIIM is established, and the theoretical analysis is carried out. Using the characteristics of inoperability, the power grid resilience is measured from the time aspect, and the characteristics of the model are analyzed at the same time; On the basis of theoretical analysis, this paper also gives a control strategy to improve the grid resilience, which has good convenience and applicability. Finally, the theoretical analysis method is applied to a power grid example, and the correctness and effectiveness are verified. The measurement model can intuitively display the resilience characteristics of power grid, and provide theoretical support for management and emergency response.